2014
DOI: 10.1113/jphysiol.2014.274498
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin enhances invasion of malignant glioma into the brain parenchyma by inducing cells to undergo amoeboid migration

Abstract: Key pointsr Glioma multiforme is a fast expanding and aggressive type of brain tumour that invades healthy brain tissue by migration of single glioma cells along blood vessels.r We show that bradykinin, a neuropeptide of the vasculature, induces the formation of small bleb-like protrusions at the plasma membrane of glioma cells in vitro, which are regulated by intracellular Ca 2+ , resulting in contraction of the cytoskeleton, cytoplasmatic flow and activation of Ca 2+ -dependent K + and Cl − channels.r From o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 31 publications
0
56
0
Order By: Relevance
“…In vivo studies on kinin B1 (B1R) and B2 receptors (B2R) revealed that B2R was increasingly expressed with augmenting malignancy of glioma (16) and GBM cells (26). Reportedly, B1R was not relevant for GBM cell invasion (15); however, B1R expression upregulation in GBM cells was confirmed by Lu et al (27). In GBM tissue, B1R expression may be induced by high levels of inflammatory cytokines produced by tumor infiltrating immune cells (28).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In vivo studies on kinin B1 (B1R) and B2 receptors (B2R) revealed that B2R was increasingly expressed with augmenting malignancy of glioma (16) and GBM cells (26). Reportedly, B1R was not relevant for GBM cell invasion (15); however, B1R expression upregulation in GBM cells was confirmed by Lu et al (27). In GBM tissue, B1R expression may be induced by high levels of inflammatory cytokines produced by tumor infiltrating immune cells (28).…”
Section: Discussionmentioning
confidence: 79%
“…With respect to the underlying mechanism, Montana and Sontheimer (16) showed that bradykinin via B2R-induced [Ca 21 ] i transients enhanced and directed invasion of glioma cells toward blood vessels. Moreover, Seifert and Sontheimer (15) recently revealed that bradykinin through [Ca 21 ] i transients in GBM cells in vitro induced the formation of small bleb-like protrusions at the plasma membrane, which stimulated an amoeboid phenotype of cell migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a critical attractor of glioma cells toward the vasculature, and an activator of ion channels (127,129). Binding of bradykinin to B 2 R leads to increases in intracellular Ca 2 + which induces the opening of the KCa3.1 and ClC-3 channels, resulting in the efflux of Cl − , K + , and water (16,127,130). As a result, the glioma cells shrink which enable them to migrate through the narrow space of the brain.…”
Section: Hydrodynamic Model Of Glioma Cell Migrationmentioning
confidence: 99%
“…63,71,109 Effectiveness of the RMP-7 and carboplatin regimen was investigated in Phase I (2001) and Phase II (2006) clinical trials, which concluded that this combination was ineffective. 164,165 Recent research indicates that glioma invasion can be achieved through a bradykinin-mediated chemotactic process, 112,144 and this finding questions the overall efficacy of using a kinin agent. Nevertheless, kinin agents continue to remain an active area of translational research, 46 particularly because of the advantage of preferential BTB disruption observed with these vasoactive compounds.…”
Section: Chemical-mediated Disruptionmentioning
confidence: 99%